Adoption of International Standards and Their Impact on The Effectiveness of The Marketing Strategies of Tourism Institutions - Asst. Prof. Dr. Alaa Abd Al Hussein Radhi (Periodica Journal, 2022)
The research aims to know the impact of the international standards ISO 9000 in achieving the Effectiveness of marketing strategies of tourism institutions and the extent to which tourism institutions adopt this concept. In order to give a statistical description of the sample surveyed, and the research reached a set of conclusions, the most important of which was that the application of the internationally agreed upon quality system (ISO 9000) in tourism institutions enables these institutions continuity in the market and to a set of recommendations, the most important of which was the need to pay attention to continuous improvement and put customer satisfaction in the list of priorities to achieve satisfactory goals
Keywords: International; standards; strategies; Institutions